KARAKTERISASI BAKTERI SALURAN PENCERNAAN IKAN NILA (Oreochromis niloticus) - Zinvie Carlina; Ummul Firmani; Saidah Luthfiyah (Universitas Muhammadiyah Gresik, 2020)
The exploration of bacteria needs to be done because of different habitats or aquatic environmental conditions, but also it is different for bacterial communities found in the digestivetract of fish. In the Gresik area, exploration of bacterial communities in the digestive tract, especially tilapia, has not been widely carried out. This study aims to determine the colony ofmorphology, cells, and gram characters of bacteria in the digestive tract of tilapia. As well as the optimal pH and temperature in bacterial rejuvenation. The research was conducted in the KaVe laboratory (Kampung Vannamei), the research procedure is the manufacture of media for bacterial growth, gram staining to determine the properties of bacteria, bacterial growth at different temperatures and pH. In this study, the results of colony morphological characterization of all isolates were round, all surface shapes were raised, the edges for NL 1isolates were irregular, NL 2 was wavy, and NL 3 was irregular. The color of all isolates is white for NL 1, which is yellowish white. And the size of the isolates was NL 1 4 µm, NL 2 8 µm,and NL3 5.65 µm. The rejuvenation results with ph showed no significant difference, while the temperature treatment showed significantly different results, namely the NL 1 and NL 3treatments with optimal temperatures of 27.2 OC and 31.7 OC. The results of this study still need further tests on identification based on biochemical characteristics and bacterial DNAtesting using PCR techniques and testing the ability of bacteria using substrates.